2023
DOI: 10.14202/vetworld.2023.1576-1583
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characteristics of Plasmodium juxtanucleare in layer chicken from three districts of Yogyakarta, Indonesia

Abstract: Background and Aim: Blood parasite infections in poultry, such as Plasmodium, are a serious threat to the poultry industry due to their potential to cause economic losses. To date, there has been inadequate research on the morphological and molecular detection of the different Plasmodium species that infect poultry in Indonesia. Therefore, this study aimed to analyze the morphological and molecular characteristics of Plasmodium spp. and the several predisposing factors for Plasmodium infection in layer chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The presence of this parasite was detected among all enrolled bird species. Several Plasmodium species have been reported from birds, including poultry and farmed birds such as Plasmodium durae, Plasmodium gallinaceum, P. relictum, and P. juxtanucleare [13]. During the present study, DNA sequencing followed by BLAST analysis confirmed the presence of P. relictum in local quails.…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…The presence of this parasite was detected among all enrolled bird species. Several Plasmodium species have been reported from birds, including poultry and farmed birds such as Plasmodium durae, Plasmodium gallinaceum, P. relictum, and P. juxtanucleare [13]. During the present study, DNA sequencing followed by BLAST analysis confirmed the presence of P. relictum in local quails.…”
Section: Plos Onesupporting
confidence: 68%
“…Additionally, over 250 species of haemosporidians parasites, including Plasmodium, Haemoproteus, Leucocytozoon, and Fallisia, have been reported in birds [11]. Avian malarial parasites, specifically avian Plasmodium, are capable of developing and completing their life cycles in various bird species and their invertebrate vectors [12,13]. Mosquitoes from the Culicidae family, including genera such as Culex, Coquillettidia, Aedes, Mansonia, Culisetta, Anopheles, and Psorophora, are involved in the transmission of these parasites [14].…”
Section: Introductionmentioning
confidence: 99%